2021
DOI: 10.3389/fmicb.2021.748706
|View full text |Cite
|
Sign up to set email alerts
|

Francisella tularensis Outer Membrane Vesicles Participate in the Early Phase of Interaction With Macrophages

Abstract: Francisella tularensis is known to release unusually shaped tubular outer membrane vesicles (OMV) containing a number of previously identified virulence factors and immunomodulatory proteins. In this study, we present that OMV isolated from the F. tularensis subsp. holarctica strain FSC200 enter readily into primary bone marrow-derived macrophages (BMDM) and seem to reside in structures resembling late endosomes in the later intervals. The isolated OMV enter BMDM generally via macropinocytosis and clathrin-dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 65 publications
2
13
0
Order By: Relevance
“…[ 53–55 ] OMVs, being extracellular nanovesicles released by bacteria, exhibit heterogeneity in size (40–300 nm diameter), [ 11,56–60 ] where the size dictates both the entry into host cells and the protein composition. [ 61–63 ] In our investigation, we noted that a fraction of orally administered A. muciniphila OMVs evades uptake during the journey from the gut to the brain, escaping uptake by other cell types and ultimately being taken up by microglial cells. We propose that a specific subset of OMVs possesses both an “eat me” signal tailored for brain microglial cells and a “do not eat me” signal that is universal for resident cells such as macrophages in other tissues.…”
Section: Discussionmentioning
confidence: 86%
“…[ 53–55 ] OMVs, being extracellular nanovesicles released by bacteria, exhibit heterogeneity in size (40–300 nm diameter), [ 11,56–60 ] where the size dictates both the entry into host cells and the protein composition. [ 61–63 ] In our investigation, we noted that a fraction of orally administered A. muciniphila OMVs evades uptake during the journey from the gut to the brain, escaping uptake by other cell types and ultimately being taken up by microglial cells. We propose that a specific subset of OMVs possesses both an “eat me” signal tailored for brain microglial cells and a “do not eat me” signal that is universal for resident cells such as macrophages in other tissues.…”
Section: Discussionmentioning
confidence: 86%
“…The MVs of Francisella tularensis were reported to be involved in the entry of the bacteria into macrophages. 135 Furthermore, dysbiosis enables the overgrowth of harmful bacteria in the gut, resulting in the increased secretion of their MVs in the gut lumen. Studies have also shown that IBD patients exhibited elevated levels of MVs in their feces compared to healthy individuals, 142 which has been attributed to the dysbiotic gut microbiota associated with IBD.…”
Section: Mvs and Their Potential Role In Ibdmentioning
confidence: 99%
“…Francisella tularensis bEVs were found to be involved in the entry mechanism of the bacteria into macrophages. 78 Secondly, bEVs induce immune responses against pathogens in macrophages. bEVs secreted by Paracoccidioides brasiliensis induced the production of proinflammatory mediators and M1 polarization in murine macrophages.…”
Section: Bevs In Inducing Host Cells Fighting Against Infectionmentioning
confidence: 99%
“…Firstly, bEVs play a role in entrance and spreading of pathogens and act directly on macrophages. Francisella tularensis bEVs were found to be involved in the entry mechanism of the bacteria into macrophages 78 . Secondly, bEVs induce immune responses against pathogens in macrophages.…”
Section: Introductionmentioning
confidence: 99%